Managerial Challenges with Knowledge Sharing A case study at a consultancy firm within the construction industry - Rybo Molin, Malin; DAHLBERG, ELIN (My University, 2018)
During the recent years, organisation’s interest in knowledge as a corporate asset has increased. More companies realize the importance of managing and invest in the knowledge within their organisation. The cornerstone of many knowledge management strategies is knowledge sharing, the process of sharing knowledge between individuals. This case study aims to analyse the knowledge sharing at a consultancy firm within the construction industry, Company A. The objective is to get an overview of the culture, processes and management in the firm, and to identify factors that facilitates, or hinder, knowledge sharing. This was possible through observations, interviews and discussions with the employees and management in Company A. The result showed that Company A has a culture of collaboration, trust and problem seeking, which are all factors that facilitate knowledge sharing. Moreover, the company has organised processes that could support employees to share their knowledge, but due to lack of time and priority, the benefits of the processes is not reached. Many factors show that most of the barriers with knowledge sharing within Company A can be associated with the organisational management. The key managerial challenges that was identified in this study was lack of time for knowledge sharing, lack of control over knowledge sharing processes, no strategy or incentives for knowledge sharing, and that the employees who possess most knowledge is often the most busy.
Keywords: Samhällsbyggnadsteknik; Civil Engineering